Semiotic Analysis of Icon and Symbol Found on Ed’s Heinz Video Advertisement - Artawan, I Made Alit; Irwandika , Gede (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study aimed to explain and examine the semiotic process as well as the meaning of icon and symbols in Ed' Heinz advertisement videos. The triadic semiosis concept from Charles Sanders Pierce's theory (1991) is used to identify and analyze data that focuses on representamen, object, and interpretant. This research used qualitative research as the method of collecting data which was downloaded from a Youtube Heinz video advertisement, a brand of ketchup produced by the H.J. HEINZ Company from the United States and has been exporting the ketchup all over the world. The result reveals that 16 Icons and 4 Symbols were found in the 3 scenes on Ed’ Heinz Video Advertisement. According to the results analysis, every components of the commercials have different meanings and interpretations.